Doença periodontal correlacionada ao autocuidado e educação regular em pacientes com síndrome de down - SOUSA, Joana Albuquerque Bastos de (2022)
Down Syndrome (DS) is a genetic condition caused by an error in the chromosome pair 21. It is characterized by changes in cognitive, physical and behavioral development, the which can directly compromise the performance of daily activities. regular schools and/or Trained professionals can improve these children with practical skills that help them in carrying out these activities. Patients with DS have a greater predisposition to Periodontal Disease (PD), which manifests itself in a generalized way, with rapid progression and with more severity. Objective: To explore whether there is a relationship between periodontal disease, self-care and education regular in patients with DS. Methods: It is a cross-sectional observational study, carried out with 49 patients with DS, 22 men and 27 women. Data collection was performed at the clinic Dentistry of the Dentistry Course at the Federal University of Maranhão (UFMA). Initially, a questionnaire was applied to obtain sociodemographic data and the evaluation of the level of functional independence of the patients, and after a clinical oral examination was performed to obtain the following periodontal clinical parameters: probing depth (PS), clinical attachment level (NIC), gingival bleeding index (ISG), and visible plaque index (IPV).Result: Our sample is represented by the mean age of 23.4 ± 9.1 years, have family income mostly between 1 and 3 minimum wages (57.1%), and with 42.8% of those responsible having a level of education up to high school. Regarding to reports of oral hygiene, 65.3% of the sample performed toothbrushing at least 3 times a day and also reported that they used dental floss with a frequency of 46.9%. Our data revealed that 38.8% of participants had moderate periodontitis and 24.5% had severe periodontitis. Regarding self-care, it was observed that the highest frequencies are related to: eating alone (91.8%), using the bathroom alone (91.8%), dressing alone home (85.7%) and using the phone alone (53.06%). The hygiene orientation experience oral cavity contributed to increase the daily brushing frequency (SRC = .280, SE = .134, P = .036), and it was observed that greater functional independence is associated with less periodontal compromise. It was also noted that the older the individual, the greater the compromised periodontal condition (P <.001). Conclusion: The findings suggest that self-care is a factor that can positively influence periodontal health, which has also been directly influenced by the age of the volunteers. Furthermore, our sample did not show direct relationship between regular or special education and better periodontal parameters. Although, a direct relationship was observed between better sociodemographic status and the frequency present or passed in regular education.